Comparison Study on Teachers’ and Parents’ Assessment of Public Participation in Basic Educational Programs Development - Vachkov, I.; Vachkova, S.N.; Voropaev, M.V.; Zadadaev, S.A.; Remorenko, I.M. (Psihologičeskaâ nauka i obrazovanie, 2016)
This research took place in 74 regions of Russian Federation. 9772 teachers and 4565 parents participated in this study. The aim of the research was to observe the assessment made by teachers and parents (legal representatives) about the degree of public participation in basic educational programs development. The subjects filled specially designed questionnaires. These questionnaires had small differences for teachers and parents. The main assessment criteria of public participation in educational institutions activity were the frequency of approaches to parents (legal representatives) on various issues, their estimation and level of satisfaction in education and personal development methods performed by educational organizations. According to the obtained data, all of the described assessment criteria statistically significantly differ between teachers and parent (legal representatives). The majority of teachers do not approve parents’ attempts to influence the content, specification and methods of education and personal development. On the contrary, parents declare their readiness to do so, while sometimes their requests are unfounded. В статье рассматривается проблема оценки педагогами и родителями общественного участия в разработке основных образовательных программ. Гипотеза состояла в том, что оценки педагогами и родителями общественного участия в разработке основных образовательных программ имеют существенные различия; при этом педагоги менее доверяют компетенциям родителей в отношении их участия в деятельности образовательной организации, чем сами родители, имеющие неадекватно завышенную самооценку своих возможностей. В исследовании, проведенном в 74 регионах России, приняли участие 9772 педагога и 4565 родителей. Использовались специально разработанные анкеты. Основными критериями оцен- ки выступили частота обращений образовательных организаций к родителям по тем или иным вопросам, учет их мнений и удовлетворенность методами обучения и воспитания. По всем критериям оценки педагогов и родителей статистически значимо различаются. При этом большинство педагогов не считают правильными попытки родителей оказывать влияние на содержание образования, условия обучения, формы и методы обучения и воспитания, в то время как родители не всегда обоснованно заявляют о готовности к этому.